Microscopic and phytochemical techniques as a tool for authentication of herbal drug chiraita: Swertia cordata (G. Don) C.B. Clarke. Issue 7 (21st March 2019) - Rashid, Sofia; Ahmad, Mushtaq; Zafar, Muhammad; Sultana, Shazia; Ahmad, Sidra Nisar; Yaseen, Ghulam; Ozdemir, Fethi Ahmet; Afza, Rabia
Abstract: Swertia cordata (G. Don) C.B. Clarke is one of the potential medicinal plants extensively used in eastern traditional medicine such as Unani, Ayurveda, Siddha, and in traditional Tibetan and Chinese medicine. S. paniculata is the common adulterant of S. cordata at herbal shops and markets but S. paniculata is also used in number of herbal formulations. The present study was conducted to use microscopic, pharmacognostic, and phytochemical techniques as a tool for the authentication of herbal drug chiraita ( S. cordata ). In herbal markets, mixing, adulteration, and use of spurious materials as substitute have become a major concern for herbal practitioners, local user, and industry for reasons of safety and efficacy. Therefore, authentication of medicinal plants is of utmost importance at each level of drug research. In the present study, anatomical features of two species showed a great diversity, as irregular epidermal cells and nonglandular, unicellular trichomes were found in S. cordata while in S. paniculata epidermal cells were hexagonal in shape and trichomes were A‐shaped. Antioxidant activity of two species showed a great variation where IC50 value recorded for S. cordata was 208 μg/mL, while for S. paniculata IC50 was 624 μg/mL. The study can serve as an important source of information to achieve the authenticity and to evaluate the quality and purity of the plant material in accordance to WHO guidelines. As this species is greatly exploited, so conservation is highly recommended. Abstract : Microscopic and Phytochemical parameters are potentially significant for the standardization of herbal drug Swertia cordata in comparison with its adulterant. The outcome of this study could be helpful in identification of genuine drug and also contribute towards establishing pharmacopoeial standards.